Nudging consumers toward healthier diets: Evidence from the Food Choice App in India - Demont, Matty; Ynion, Jhoanne; Custodio, Marie Claire; Ray (Chakravarti), Anindita; Samaddar, Arindam; Kanta, Mohanty Suva (Oxford University Press, 2025)
We develop the Food Choice App (FCA) based on the Gastronomic Systems Research (GSR) framework to study how behavioral change communication (BCC) on healthier diets influences diet planning under income shocks. A sample of 192 low- and middleincome households in West Bengal use the FCA to plan their diets by allocating a randomized weekly food budget among 162 Bengali dishes across five eating occasions over seven weekdays. Budget constraints drive carbohydrate prioritization, but BCC exposure and women’s empowerment significantly increase dietary protein density. Findings underscore the importance of targeted nudges across multiple levels of the Gastronomic System to promote healthier diets.